The effect of dissolution medium, rotation speed and compaction pressure on the intrinsic dissolution rate of amlodipine besylate, using the rotating disk method - Leandro Giorgetti; Michele Georges Issa; Humberto Gomes Ferraz (Universidade de São Paulo, 2014)
The aim of this study was to evaluate the effect of dissolution medium, rotation speed and compaction pressure on the intrinsic dissolution rate (IDR) of the antihypertensive drug amlodipine besylate, using the rotating disk method. Accordingly, a fractional factorial design (33-1) was used, employing dissolution media (water, phosphate buffer pH 6.8 and HCl 0.1 M), rotation speed (50, 75 and 100 rpm), and compaction pressure (1000, 1500 and 2000 psi) as independent variables. The assays were randomized and statistically compared using the Statistica(r) 11 software program. Significance testing (ANOVA) indicated that the dissolution medium had a considerable impact on the IDR of amlodipine besylate. Analysis of the linear and quadratic components of the variables led to the proposition of a mathematical model that describes the IDR as a function of the parameters studied. Conversely, the levels of compaction pressure and rotation speed employed during experimental planning were less relevant, especially when the assay was conducted in the HCl 0.1 M medium.